Circumcision, can this procedure be dangerous for the patient? - Mehdi Fathi; Mahdi Parvizi Mashhadi; Alireza Sabzevari; Mohammad Mehdi Zarif soltani; Alireza Ghodsi; Marjan Joodi (Elsevier, 2021)
Circumcision is one of the most common surgical operations, which is usually a safe and simple procedure with rare complications. Amputation of glans is an uncommon condition but has definitive risk of complication. It's crucial to consider patients based on their age and anatomical conditions, as well as undertaking well sterile surgery for preventing any future complications of circumcision.In this study we have investigated a complete glans amputation during the circumcision that was initially repaired and the result was good.